2021
DOI: 10.1080/1547691x.2021.1922957
|View full text |Cite
|
Sign up to set email alerts
|

Serum vaccine antibody concentrations in adults exposed to per- and polyfluoroalkyl substances: A birth cohort in the Faroe Islands

Abstract: Per-and polyfluoroalkyl substances (PFASs) are highly persistent in the environment and may cause depressed immune function. Previous studies have linked PFAS exposure to lower vaccine responses in children, but research in adults is limited. Therefore, the present study evaluated the associations between exposure to PFASs and serum antibody concentrations in adults vaccinated at age 28 years in the Faroe Islands. PFAS concentrations were determined from cord-blood collected at birth and serum samples collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…The U.S. Environmental Protection Agency (EPA) has recently issued a draft systematic review of antibodies other than to COVID-19 for consideration by its Scientific Advisory Board and preliminarily concluded that there was an inverse association for PFOA and PFOS in children ( US EPA, 2022 ). Some of the data on antibody concentrations after vaccination in relation to PFAS in adults have provided support for an inverse association ( Kielsen et al, 2016 , Looker et al, 2014 , Pilkerton et al, 2018 , Shih et al, 2021 ; Stein, Ge, et al, 2016; Stein, McGovern, et al, 2016); however, limited data exist on any given vaccine type. Large differences in Coronavirus antibody concentrations affect risk of Coronavirus disease ( Barrow et al, 1990 , Bradburne et al, 1967 , Callow, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Environmental Protection Agency (EPA) has recently issued a draft systematic review of antibodies other than to COVID-19 for consideration by its Scientific Advisory Board and preliminarily concluded that there was an inverse association for PFOA and PFOS in children ( US EPA, 2022 ). Some of the data on antibody concentrations after vaccination in relation to PFAS in adults have provided support for an inverse association ( Kielsen et al, 2016 , Looker et al, 2014 , Pilkerton et al, 2018 , Shih et al, 2021 ; Stein, Ge, et al, 2016; Stein, McGovern, et al, 2016); however, limited data exist on any given vaccine type. Large differences in Coronavirus antibody concentrations affect risk of Coronavirus disease ( Barrow et al, 1990 , Bradburne et al, 1967 , Callow, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PFAS exposures and biomarkers of immunomodulation such as vaccine responses in humans has been investigated in 13 studies. These include six birth cohort studies conducted in Norway (Granum et al 2013), the Faroe islands (Grandjean et al 2012(Grandjean et al , 2017aShih et al 2021), Germany (Abraham et al 2020), and China (Zeng et al 2019); one longitudinal analysis of adult residents in the US state of West Virginia with higher PFOA levels in drinking water (Looker et al 2014); three crosssectional studies based on data from the US National Health and Nutrition Examination Survey (NHANES) (Stein et al 2016a, b), a study using adult volunteers from a hospital in Denmark (Kielsen et al 2016), one study using cross-sectional data from the cohort Isomer of C8 Health Project in China (Zeng et al 2020) and a prospective study based on a subset of data from a randomized controlled trial conducted in West Africa (Timmermann et al 2020).…”
Section: Vaccine Responsementioning
confidence: 99%
“…Seven studies (Abraham et al 2020;Grandjean et al 2012Grandjean et al , 2017aGranum et al 2013;Kielsen et al 2016;Shih et al 2021) examined tetanus antibody concentrations. Diphtheria antibody concentrations were examined in five studies (Abraham et al 2020;Grandjean et al 2012Grandjean et al , 2017aKielsen et al 2016;Shih et al 2021).…”
Section: Vaccine Responsementioning
confidence: 99%
See 2 more Smart Citations